Governance Structures and Processes in Interorganizational Collaboratives: The Critical Role of Power and Equity - Whitley, Meredith A.; Svensson, Per G. (Administration in social work, 2025)
Interorganizational collaboratives among human service nonprofit organizations are potential hubs for innovation and progress. The purpose of this study was to explore the role of governance in an interorganizational collaborative, the "Sport for Good Cities" initiative, which was intentionally designed to achieve collective impact. Drawing on interviews with 30 stakeholders, the findings provide important theoretical and practical insights for governance in interorganizational collaboratives in terms of the central role and challenges related to power and decision-making, backbone support, and equity and engagement. For example, the findings highlight the need to decide how collaboratives will be governed during the formative stages of interorganizational endeavors, along with governance structures and processes that deconstruct systemic and structural inequities.